Kejayaan Abbasiyah: Pembentukan Sistem Kerajaan yang Mengubah Sejarah - Rachman, Muhammad Aditya; Hasaruddin, Hasaruddin (Universitas Negeri Makassar, 2023)
This research examines the development of Islamic education from the era of Prophet Muhammad SAW through three significant regimes - Khulafaur Rasyidin, Umayyad, and Abbasid - with a special focus on the Abbasid period. It studies how Islamic education evolved from the foundational phase during Prophet Muhammad's time, through its developmental phase in the Khulafaur Rasyidin era, to its zenith during the Abbasid dynasty, known as the golden age in all fields, including education. This study delves into how Islamic educational institutions flourished and played a role in creating new civilizations and cultures among Muslims. This research hopes to inspire the modern Muslim community to adapt and modify effective educational approaches, creating better and more effective educational institutions to prepare students for the future.